(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe clinical and radiographic characteristics of the group with chronic periapical periodontitis in the anterior teeth at the Department of Maxillofacial Dentistry, Hai Phong University Hospital, in 2025-2026. To evaluate treatment outcomes using BioRoot sealer in the aforementioned patient group. Subject and research methods: The study was conducted on 35 anterior teeth of 35 patients with chronic periapical periodontitis of the anterior teeth, who were examined and treated at the Department of Odonto-Stomatology, Hai Phong University Hospital of Medicine, from October 2025 to April 2026. The study was designed as a longitudinal follow-up. Results and conclusions: The homogeneous root canal filling mass (accounting for 94.3%) is higher than the filling mass with voids (accounting for 5.7%). Immediately after root canal obturation, good outcomes were higher than average and poor outcomes, with good results accounting for 94.2%. Six months after root canal obturation with BioRoot sealer, the rate of treatment showing signs of healing on periapical X-ray was 85.7%, only 14.3% were showing signs of healing, and no cases showed no signs of healing.